The impact of cultural frame switching on wellbeing- systematic review - Eshia Garcha; Amber Qureshi; Ciarán O’Driscoll; Madiha Shaikh (PLoS ONE, 2025)
Objective This pre-registered review synthesised findings from studies examining individuals’ experiences of cultural frame switching (CFS) and its potential impact on well-being. Background CFS is a strategy used by bi/multicultural individuals to navigate daily life by shifting between cultural frameworks in response to environmental cues, influencing thoughts, emotions, and behaviours. Method Eleven studies were identified through systematic searches across four electronic databases, with a total sample size of 2,657. The JBI approach to qualitative synthesis was applied, alongside evidence synthesis for the quantitative findings. Results The findings suggest that CFS may influence well-being in both positive and negative ways. Potential benefits include enhanced personal relationships, workplace well-being and success, cultural adjustment, and identity navigation. However, CFS may also contribute to identity conflict and associated distress, lower satisfaction with life, perceived discrimination, reduced self-esteem, diminished authenticity, and increased psychological symptoms such as anxiety and low mood. Conclusions While CFS appears to have both beneficial and adverse effects on well-being, the limited research in this area makes it difficult to draw definitive conclusions. Further investigation is needed to better understand these mechanisms, why certain individuals experience more challenges, and how to mitigate potential negative impacts. Expanding research in this area could inform future models of support for individuals from minority and multicultural backgrounds.